2012
DOI: 10.1093/humrep/des234
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a panel of 28 biomarkers for the non-invasive diagnosis of endometriosis

Abstract: In plasma samples obtained during menstruation, multivariate analysis of four biomarkers (annexin V, VEGF, CA-125 and sICAM-1/or glycodelin) enabled the diagnosis of endometriosis undetectable by US with a sensitivity of 81-90% and a specificity of 63-81% in independent training- and test data set. The next step is to apply these models for preoperative prediction of endometriosis in an independent set of patients with infertility and/or pain without US evidence of endometriosis, scheduled for laparoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
165
2
12

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(189 citation statements)
references
References 74 publications
4
165
2
12
Order By: Relevance
“…Increased serum IL-6 levels observed in patients with minimal-mild endometriosis in our study are in line with findings of some reports [18][19][20] but depart from others that found no value for serum IL-6 in the diagnosis of endometriosis at any stage [21,22] and from yet others that reported slightly elevated serum IL-6 levels in controls [23][24][25]. Additionally, it is worthwhile to note that serum IL-6 was the only marker that was constantly elevated in all our comparison groups (endometriosis group, minimalmild endometriosis group and moderate-severe endometriosis group).…”
Section: Discussionsupporting
confidence: 90%
“…Increased serum IL-6 levels observed in patients with minimal-mild endometriosis in our study are in line with findings of some reports [18][19][20] but depart from others that found no value for serum IL-6 in the diagnosis of endometriosis at any stage [21,22] and from yet others that reported slightly elevated serum IL-6 levels in controls [23][24][25]. Additionally, it is worthwhile to note that serum IL-6 was the only marker that was constantly elevated in all our comparison groups (endometriosis group, minimalmild endometriosis group and moderate-severe endometriosis group).…”
Section: Discussionsupporting
confidence: 90%
“…18 More recently it was reported that in plasma samples obtained during menstruation, multivariate analysis of 4 biomarkers (annexin V, VEGF, CA-125, and sICAM-1/or glycodelin) enabled the diagnosis of endometriosis undetectable by ultrasound with a sensitivity of 81% to 90% and a specificity of 63% to 81% in independent training and test data sets. 19 Peptide fingerprinting using proteomic analysis of plasma may also have utility as a noninvasive or semi-invasive diagnostic for endometriosis. 20 Taken together, these data suggest that endometriosis biomarkers can be developed using a panel of ''known'' biomarkers or by the discovery of new biomarkers based on proteomic, microarray, metabolomic analysis, or other systems biology approaches.…”
Section: Diagnosismentioning
confidence: 99%
“…Однако ни один биомаркер, ни панель биомар-керов не утверждена в качестве надежного неинва-зивного метода диагностики эндометриоза [29,30]. Возможно, это связано с тем, что большинство ис-следований включали ограниченное число пациен-ток, проводились в различные фазы менструального цикла, не оценивалась стадия заболевания и локали-зация поражений (перитонеальная форма, инфиль-тративный эндометриоз, эндометриоидная киста яичника).…”
unclassified
“…[30] про-веден многомерный анализ 28 биомаркеров. Авторы изучали биомаркеры в плазме крови у женщин с хи-рургически подтвержденным диагнозом эндометри-оза и без такового (контрольная группа).…”
unclassified
See 1 more Smart Citation